Student Motivation in Learning PJOK: A Study on Lower Passing Volleyball - Widiatma, Akhmad Arif; Hasmyati, Hasmyati; Asran, Asran (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This paper aims to find out how students' motivation to learn improves skills in learning volleyball underpassing in learning PJOK. In this study, researchers used a qualitative approach. The data was taken through the interview method. The study selected participants taken from fifth-grade students at MIN 5 Ngawi, East Java, Indonesia. The technique used is Provosive Sampling. Data sources are taken with certain considerations. In this technique, the person who is considered to know best about what we expect is given consideration. Data analysis used reduction data, display data, and conclusion. The results showed that motivation affects learning outcomes. While the award provides stimulation from the outside to participate in learning.